2022
DOI: 10.3390/ijerph192013225
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis of COVID-19 Vaccination Factors among Native and Foreign-Born Hispanic/Latine Adults Residing in South Florida, U.S.A.

Abstract: This study explored barriers, motivators, and trusted sources of information regarding COVID-19 vaccination among Hispanic/Latine individuals. Hispanic/Latine is a broad social construct that encompasses people from heterogeneous countries and cultures. In the U.S., foreign-born Hispanics/Latines tend to have better health outcomes than U.S.-born individuals. Thus, the study examined whether nativity is a significant factor in COVID-19 vaccine hesitancy. Binary logistic regression and linear regression analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…This finding was consistent with other research suggesting that greater income was related to lower vaccine hesitancy (in parents) and a greater likelihood of COVID-19 vaccination (in parents) [ 17 ]. We found that nativity was unrelated to COVID-19 vaccine hesitancy, and this is in line with some previous work that suggests no difference in vaccine hesitancy between foreign-born Hispanics and US-born Whites [ 48 , 49 ]. Although our study sample was entirely Hispanic/Latinx, it is plausible that other factors may offset differences in COVID-19 hesitancy between US-born and foreign-born participants.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was consistent with other research suggesting that greater income was related to lower vaccine hesitancy (in parents) and a greater likelihood of COVID-19 vaccination (in parents) [ 17 ]. We found that nativity was unrelated to COVID-19 vaccine hesitancy, and this is in line with some previous work that suggests no difference in vaccine hesitancy between foreign-born Hispanics and US-born Whites [ 48 , 49 ]. Although our study sample was entirely Hispanic/Latinx, it is plausible that other factors may offset differences in COVID-19 hesitancy between US-born and foreign-born participants.…”
Section: Discussionsupporting
confidence: 92%
“…[19][20][21] In addition, research shows that collective responsibility plays a role in COVID-19 vaccine acceptance among Hispanic people and that Hispanic people are more likely than black people to report having a friend or family member who had or died from COVID-19. 19,22,23 Therefore, it could be that a sense of responsibility to protect their families and communities may have motivated Hispanic participants to get vaccinated.…”
Section: Discussionmentioning
confidence: 99%